若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 17:53:34
若m-n=-3mn=2则(-5m+2)-5(2mn-n)=若m-n=-3mn=2则(-5m+2)-5(2mn-n)=若m-n=-3mn=2则(-5m+2)-5(2mn-n)=若m-n=-3mn=2则(
若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=
若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=
若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=
若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=
(-5m+2)-5(2mn-n)
=-5m+2-10mn+5n
=-5(m-n)-10mn+2
=-5*(-3)-10*2+2
=15-20+2
=-3
解(-5m+2)-5(2mn-n)
=-5m+2-10mn+5n
=-5m+5n+2-10mn
=-5(m-n)-10mn+2
=-5×(-3)-10×2+2
=15-20+2
=-3
若(m+n)^2-mn(m+n)=(m+n)·M,则M是() A.m^2+n^2 B.m^2-mn+n^2 C.m^2-3mn+n^2 D.m^2+mn+n^2
若m-n=4,mn=-1,求(-2mn+m+n)-(3mn+5n-5m)-(m+4n-3mn)的值
m+n=5,mn=14,则(3m-2n)-(-5n+mn)
1/M+1/N=5 (3M+MN+2N) / (M-MN=3N)
若M-N=5,MN=-2,则(N-M)的平方-4MN=
若m+n=0,则多项式m^3-m^3n-mn^2+n^3
已知mn/m+n=2求3m-5mn+3n/-m+3mn-n
已知M+N分之MN=2,求-m+3mn-n分之3m-5mn+3n
已知mn/m+n=2,求3m-5mn+3n/(-m)+3mn-n
已知mn/m+n=2,求3m-5mn+3n/-m+3mn-n的值
若m-n=-3,mn=2,则(-5m+2——-5(2mn-n)=?应该是若m-n=-3,mn=2,则(-5m+2)-5(2mn-n)=?
若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=若m-n=-3 mn=2 则(-5m+2)-5(2mn-n)=
若(m+n)(m-n)^2-mn(m+n)=(m+n)·M,则M是
已知m^2-mn=2,mn-n^2=5则3m^2+2mn-5n^2
若m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)
若m-n=4,mn=-1求(9-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)
-2(mn-3m平方)-{m平方-5(mn-m平方)+2mn,其中m=1,n=-2
m-n=7 mn=-5求(3m+5n+4mn)-(2n-4n+6mn)